China as average power in ascent to global since the first decade of the 21st century: reaches and limits - Fierro de Jesús, Tonatiuh (2016)
This article aims to analyze China's foreign policy as a rising middle power to global power and its diplomatic coverage abroad. The first part explains because China is not yet a "great global power." The second part delineates the whole outer space covered by Chinese diplomacy in a general manner outlined. The third section will mark the institutional framework in which the decisions of China's foreign policy are taken. Analyzing the Chinese case as a rising middle power to global power will be useful to clarify whether the institutional framework of its foreign policy allows or doesn´t play a prominent role in the international arena. Thus, we will learn about the scope and limits of the performance of China in the international arena